Improvement of N -phthaloylchitosan based gel polymer electrolyte in dye-sensitized solar cells using a binary salt system - Yusuf, S.N.F.; Azzahari, A.D.; Selvanathan, V.; Yahya, R.; Careem, M.A.; Arof, Abdul Kariem (Elsevier, 2017)
A binary salt system utilizing lithium iodide (LiI) as the auxiliary component has been introduced to the N-phthaloylchitosan (PhCh) based gel polymer electrolyte consisting of ethylene carbonate (EC), dimethylformamide (DMF), tetrapropylammonium iodide (TPAI), and iodine (I2) in order to improve the performance of dye-sensitized solar cell (DSSC) with efficiency of 6.36%, photocurrent density, JSC of 17.29 mA cm−2, open circuit voltage, VOC of 0.59 V and fill factor, FF of 0.62. This efficiency value is an improvement from the 5.00% performance obtained by the DSSC consisting of only TPAI single salt system. The presence of the LiI in addition to the TPAI improves the charge injection rates and increases the iodide contribution to the total conductivity and both factors contribute to the increase in efficiency of the DSSC. The interaction behavior between polymer–plasticizer–salt was thoroughly investigated using EIS, FTIR spectroscopy and XRD.